2014
DOI: 10.1002/jmri.24727
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast myocardial T1 mapping using cardiovascular magnetic resonance for iron overload

Abstract: Myocardial T1 mapping is an alternative method for cardiac iron quantification. T1 mapping shows the potential for improved detection of mild iron loading. The superior reproducibility of T1 has potential implications for clinical trial design and therapeutic monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 43 publications
10
108
2
1
Order By: Relevance
“…91,106,107 From a clinical perspective, T1 indices can support differentiation of the infiltrative hypertrophic phenocopies in suspected cardiac amyloid infiltration: normal T1 indices can virtually exclude the presence of amyloid disease. On the contrary, significantly raised T1 indices point toward HCM or cardiac amyloid, 84,87,89 whereas low T1 values might raise the prospect of Fabry's disease in the appropriate setting.…”
Section: T1 Mapping In Hypertrophic Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…91,106,107 From a clinical perspective, T1 indices can support differentiation of the infiltrative hypertrophic phenocopies in suspected cardiac amyloid infiltration: normal T1 indices can virtually exclude the presence of amyloid disease. On the contrary, significantly raised T1 indices point toward HCM or cardiac amyloid, 84,87,89 whereas low T1 values might raise the prospect of Fabry's disease in the appropriate setting.…”
Section: T1 Mapping In Hypertrophic Phenotypesmentioning
confidence: 99%
“…11,45,[83][84][85][86] Abnormal T1-mapping indices were also found in other common causes of DCM, including patients with cardiac amyloidosis, [87][88][89] diabetic cardiomyopathy, 34,90 and iron overload cardiomyopathies. 91 Native T1 mapping may also become of utility in patients with congenital heart disease and heart transplantation for rejection, 44,92,93 whose monitoring currently relies on repetitive invasive investigations. In a multicenter observational study, native T1 and ECV have been shown to be stronger predictors of poor outcome in DCM than classic parameters, 11 whereby native T1 was the strongest independent predictor of all-cause mortality and development of HF LGE− 27±3 0.6…”
Section: T1 Mapping In Nonischemic Dilative Cardiomyopathymentioning
confidence: 99%
“…Such myocardial pathologies detectable by CMR include focal scarring of either ischemic or nonischemic origin, [32][33][34] diffuse fibrosis, 35 edema, 36,37 inflammation, 38 fatty infiltration, 39 or abnormal myocardial deposition of substances such as amyloid protein, [40][41][42] glycolipids, 43 and iron. 44,45 As mentioned above, the increased mass in LVH is not solely the result of an increased amount of normal tissue. In less common cases, hypertrophy may be related to abnormal myocardial deposition of glycolipids, iron or amyloid, which also may affect ECG.…”
Section: Cmr Assessment Of Lvh Beyond LV Massmentioning
confidence: 92%
“…This technique has been validated against pathology and represents the currently used gold standard for the non-invasive assessment of iron overload [91]. However, myocardial T1 mapping shows the potential for improved detection of mild iron loading, and its superior reproducibility has potential implications for clinical trial design and therapeutic monitoring [92]. Finally, ECV is significantly increased in thalassemia major and is associated with myocardial iron overload, as assessed by T2* [93].…”
Section: Iron Overload Diseasementioning
confidence: 99%